2015
DOI: 10.1094/phyto-06-14-0172-r
|View full text |Cite
|
Sign up to set email alerts
|

Emergence ofGroundnut ringspot virusandTomato chlorotic spot virusin Vegetables in Florida and the Southeastern United States

Abstract: Groundnut ringspot virus (GRSV) and Tomato chlorotic spot virus (TCSV) are two emerging tospoviruses in Florida. In a survey of the southeastern United States, GRSV and TCSV were frequently detected in solanaceous crops and weeds with tospovirus-like symptoms in south Florida, and occurred sympatrically with Tomato spotted wilt virus (TSWV) in tomato and pepper in south Florida. TSWV was the only tospovirus detected in other survey locations, with the exceptions of GRSV from tomato (Solanum lycopersicum) in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
21

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 38 publications
2
52
0
21
Order By: Relevance
“…Interestingly, Melon yellow spot virus (MYSV), formerly reported only in Asia, has for the first time been found outside Asia, in Ecuador (94). Furthermore, in Florida in 2012 (66), the first occurrence of a natural interspecific reassortant Groundnut ringspot virus (GRSV)-Tomato chlorotic spot virus (TCSV) in tomato fields has been reported (144) and its parental TCSV species identified. Another study performed with a number of TSWV isolates showed that reassortment among isolates within a species seems to be a common evolutionary strategy (136), and, in one case, a resistance-breaking (RB) isolate was shown to originate through reassortment (73).…”
Section: Tospovirus Diversity: New and Old Threats To Vegetable Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Melon yellow spot virus (MYSV), formerly reported only in Asia, has for the first time been found outside Asia, in Ecuador (94). Furthermore, in Florida in 2012 (66), the first occurrence of a natural interspecific reassortant Groundnut ringspot virus (GRSV)-Tomato chlorotic spot virus (TCSV) in tomato fields has been reported (144) and its parental TCSV species identified. Another study performed with a number of TSWV isolates showed that reassortment among isolates within a species seems to be a common evolutionary strategy (136), and, in one case, a resistance-breaking (RB) isolate was shown to originate through reassortment (73).…”
Section: Tospovirus Diversity: New and Old Threats To Vegetable Cropsmentioning
confidence: 99%
“…In addition to RB isolates (4, 22, 23, 62, 106), unique tospovirus isolates have been identified, arisen from genome reassortment during mixed infections (144,145). The ecological and evolutionary significance of such reassortant events, as well as the risk these resulting new viruses may pose on the durability of genetic resistance genes, remain to be elucidated.…”
Section: A New Allele Of the Sw-5 Gene Cluster And Sw-5 Analogs In Otmentioning
confidence: 99%
“…South American isolates formed a separate monophyletic group to those from Central and North America. Webster et al (2015) reported that the RNAs of TCSV isolates from Florida (USA), Puerto Rico, and the Dominican Republic all share high levels of nucleotide identity with the corresponding RNAs of TCSV isolates from South America. With regard to Brazilian TCSV, the isolate from M. jalapa (TCSV-Mir-BR07, GenBank number KP276236) formed a monophyletic group with isolates from the states of Rio Grande do Sul (JQ034525) and Minas Gerais (AF282982), as well as Argentina (U49709), in the maximum-likelihood tree.…”
mentioning
confidence: 99%
“…In Florida, thrips feeding damage has been associated with post-bloom fruit drop in citrus, fruit bronzing in strawberry, leaf distortion in pepper and other crops, and stippling in tomato (Frantz & Mellinger 1990;Childers 1999;Dŏgramaci et al 2011;Smith & Whidden 2014). Viruses in Florida transmitted by thrips include Tomato spotted wilt virus (TSWV), Tomato chlorotic spot virus (TCSV), Iris necrotic spot virus (INSV), and Groundnut ringspot virus (GRSV) (Baker et al 2007;Webster et al 2011Webster et al , 2015. Thrips species in Florida that have quarantine status elsewhere include F. occidentalis, Thrips hawaiiensis (Morgan), T.…”
mentioning
confidence: 99%